Model Prediksi Kecelakaan Kendaraan Sepeda Motor pada Ruas Jalan di Kota Ambon - Frando Simon Hukom; Ludfi Djakfar; Muhammad Zainul Arifin (Department of Civil Engineering, Faculty of Engineering, Universitas Brawijaya, 2023)
This study aims to model the prediction of motorcycle vehicle accidents in Ambon City. Factors reviewed in this study include socioeconomic and travel patterns, driving equipment and preparation, driving habits, and driving behavior. The survey was conducted using interview and questionnaire survey methods with a total of 250 respondents. The research method used is data analysis using Structural Equation Modeling (SEM). The results of motorcycle accident modeling show that the first biggest influence on the prediction of an accident is the driver's behavior characteristic variable, with the indicator that describes the cause of a traffic accident is the indicator of driving over the speed limit. Thus when a motorbike driver drives his vehicle fast and exceeds the speed limit, the higher the possibility that the driver will experience a traffic accident. So it is necessary to have cooperation between the police and related parties in dealing with accidents and reducing the risk of traffic accidents such as providing outreach or information, through newspaper or electronic media to the people in Ambon City regarding the dangers of driving over speed or speeding while driving on the road Ambon City.